Assignment 13

course Mth 158

^ύƯwƅқassignment #013

Your work has been received. Please scroll through the document to see any inserted notes (inserted at the appropriate place in the document, in boldface) and a note at the end. The note at the end of the file will confirm that the file has been reviewed; be sure to read that note. If there is no note at the end, notify the instructor through the Submit Work form, and include the date of the posting to your access page.

013. `query 13

College Algebra

07-02-2007

......!!!!!!!!...................................

11:29:44

query 1.4.12 (was 1.4.6). Explain how you found the real solutions of the equation (1-2x)^(1/3) - 1 = 0

......!!!!!!!!...................................

RESPONSE -->

I added 1 to both sides (1-2x)^1/3 = 1. Then I cubed both sides. 1 - 2x = 1. Next I subtracted 1 from both sides -2x = 0 divide by -2 and I got x = 0.

confidence assessment: 2

.................................................

......!!!!!!!!...................................

11:30:22

** Starting with

(1-2x)^(1/3)-1=0 add 1 to both sides to get

(1-2x)^(1/3)=1 then raise both sides to the power 3 to get

[(1-2x)^(1/3)]^3 = 1^3.

Since [(1-2x)^(1/3)]^3 = (1 - 2x) ^( 1/3 * 3) = (1-2x)^1 = 1 - 2x we have

1-2x=1. Adding -1 to both sides we get

-2x=0 so that

x=0. **

......!!!!!!!!...................................

RESPONSE -->

That is how I did it.

self critique assessment: 3

.................................................

......!!!!!!!!...................................

11:32:43

1.4.28 (was 1.4.18). Explain how you found the real solutions of the equation sqrt(3x+7) + sqrt(x+2) = 1.

......!!!!!!!!...................................

RESPONSE -->

First I squared both sides 3x+7 + x+2 = 1. Then I combined like terms 4x + 9 = 1. Then subtracted 9 from both sides. 4x = -8 and divided by 4 to get x = -2.

confidence assessment: 2

.................................................

......!!!!!!!!...................................

11:33:59

** Starting with

sqrt(3x+7)+sqrt(x+2)=1

we could just square both sides, recalling that (a+b)^2 = a^2 + 2 a b + b^2. This would be valid but instead we will add -sqrt(x+2) to both sides to get a form with a square root on both sides. This choice is arbitrary; it could be done either way. We get

sqrt(3x+7)= -sqrt(x+2) + 1 . Now we square both sides to get

sqrt(3x+7)^2 =[ -sqrt(x+2) +1]^2. Expanding the right-hand side using (a+b)^2 = a^2 + 2 a b + b^2 with a = -sqrt(x+2) and b = 1:

3x+7= x+2 - 2sqrt(x+2) +1. Note that whatever we do we can't avoid that term -2 sqrt(x+2). Simplifying

3x+7= x+ 3 - 2sqrt(x+2) then adding -(x+3) we have

3x+7-x-3 = -2sqrt(x+2). Squaring both sides we get

(2x+4)^2 = (-2sqrt(x+2))^2.

Note that when you do this step you square away the - sign, which can result in extraneous solutions.

We get

4x^2+16x+16= 4(x+2). Applying the distributive law we have

4x^2+16x+16=4x+8. Adding -4x - 8 to both sides we obtain

4x^2+12x+8=0. Factoring 4 we get

4*((x+1)(x+2)=0 and dividing both sides by 4 we have

(x+1)(x+2)=0 Applying the zero principle we end up with

(x+1)(x+2)=0 so that our potential solution set is

x= {-1, -2}.

Both of these solutions need to be checked in the original equation sqrt(3x+7)+sqrt(x+2)=1

It turns out that the -1 gives us sqrt(4) + sqrt(1) = 1 or 2 + 1 = 1, which isn't true, while -2 gives us sqrr(1) + sqrt(0) = 1 or 1 + 0 = 1, which is true.

x = -1 is the extraneous solution that was introduced in our squaring step.

Thus our only solution is x = -2. **

......!!!!!!!!...................................

RESPONSE -->

I just squared both sides and got -2. I see how the other way would have worked too.

self critique assessment: 2

.................................................

......!!!!!!!!...................................

11:39:53

1.4.40 (was 1.4.30). Explain how you found the real solutions of the equation x^(3/4) - 9 x^(1/4) = 0.

......!!!!!!!!...................................

RESPONSE -->

Since both parts of the equation take the fourth root, I raised both sides of the equation to the 4th power and got x^3 - 9x = 0. Then I factored out x and got

x(x^2 - 9) = 0. I set x = 0 and x^2 - 9 = 0. I then solved for x by adding 9 to both sides x^2 = 9 took the square root and got x = 3. So my answers are x = 0, 3.

confidence assessment: 1

.................................................

......!!!!!!!!...................................

11:42:46

** Here we can factor x^(1/4) from both sides:

Starting with

x^(3/4) - 9 x^(1/4) = 0 we factor as indicated to get

x^(1/4) ( x^(1/2) - 9) = 0. Applying the zero principle we get

x^(1/4) = 0 or x^(1/2) - 9 = 0 which gives us

x = 0 or x^(1/2) = 9.

Squaring both sides of x^(1/2) = 9 we get x = 81.

So our solution set is {0, 81). **

......!!!!!!!!...................................

RESPONSE -->

I got zero as an answer, but I didn't get 81. I see how x^(1/4) factors out and how you got 81 as a solution.

self critique assessment: 2

.................................................

......!!!!!!!!...................................

12:04:40

1.4.46 (was 1.4.36). Explain how you found the real solutions of the equation x^6 - 7 x^3 - 8 =0

......!!!!!!!!...................................

RESPONSE -->

I factored x^6 - 7x^3 - 8 = 0 into (x^3 - 8) ( x^3 + 1) = 0. then I set x^3 - 8 = 0 and added 8 to both sides x^3= 8 took the cube root and found x = 2. Then I set x^3 + 1 = 0 subtracted 1 from both sides and took the cube root and got x = 1.

confidence assessment: 2

.................................................

......!!!!!!!!...................................

12:05:04

** Let a = x^3. Then a^2 = x^6 and the equation x^6 - 7x^3 - 8=0 becomes

a^2 - 7 a - 8 = 0. This factors into

(a-8)(a+1) = 0, with solutions

a = 8, a = -1.

Since a = x^3 the solutions are x^3 = 8 and x^3 = -1.

We solve these equations to get

x = 8^(1/3) = 2 and x = (-1)^(1/3) = -1. **

......!!!!!!!!...................................

RESPONSE -->

I got it.

self critique assessment: 3

.................................................

......!!!!!!!!...................................

12:16:21

1.4.64 (was 1.4.54). Explain how you found the real solutions of the equation x^2 - 3 x - sqrt(x^2 - 3x) = 2.

......!!!!!!!!...................................

RESPONSE -->

I squared both sides to get x^4 - 3x^2 - x^2 - 3x = 4. Then I combined like terms and got x^4 - 4x^2 - 3x = 4. I factored out a x and got x(x^3 - 4x - 3) = 4. I set x=4 and x^3 - 4x -3=4. I factored that to (x^3 - 3) (x-1). x^3 - 3 = 4 and got x = cube rt (7). and x -1 = 4 and found x= 5. Since cube rt(7) is not a real number, the solutions for this problem are ( 4 , 5)

confidence assessment: 1

.................................................

......!!!!!!!!...................................

12:17:53

** Let u = sqrt(x^2 - 3x). Then u^2 = x^2 - 3x, and the equation is

u^2 - u = 2. Rearrange to get

u^2 - u - 2 = 0. Factor to get

(u-2)(u+1) = 0.

Solutions are u = 2, u = -1.

Substituting x^2 - 3x back in for u we get

sqrt(x^2 - 3 x) = 2 and sqrt(x^2 - 3 x) = -1.

The second is impossible since sqrt can't be negative.

The first gives us

sqrt(x^2 - 3x) = 2 so

x^2 - 3x = 4. Rearranging we have

x^2 - 3x - 4 = 0 so that

(x-4)(x+1) = 0 and

x = -4 or x = 1.

DER **

......!!!!!!!!...................................

RESPONSE -->

I got that one wrong. I see how u can equal x^2 - 3x. I understand how to rearrange the problem and get the correct solutions.

self critique assessment: 2

.................................................

......!!!!!!!!...................................

12:29:02

1.4.90 (was 1.4.66). Explain how you found the real solutions of the equation x^4 + sqrt(2) x^2 - 2 = 0.

......!!!!!!!!...................................

RESPONSE -->

Let u = x^2 so u^2 = x^4. u^2 + sqrt (2u) - 2 = 0. Then I add 2 to both sides u^2 + sqrt (2u) = 2. Then I squared both sides and got u^4 + 2u = 4. I factored out an u and found u(u^3 + 2). I set u=4 and u^3 + 2=4. subtracted 2 from both sides and got u = cube rt(2) which rounded equals 1.26. So my solutions are 4 and 1.26.

confidence assessment: 1

.................................................

......!!!!!!!!...................................

12:30:37

** Starting with

x^4+ sqrt(2)x^2-2=0 we let u=x^2 so that u^2 = x^4:

u^2 + sqrt(2)u-2=0

using quadratic formula

u=(-sqrt2 +- sqrt(2-(-8))/2 so

u=(-sqrt2+-sqrt10)/2

Note that u = (-sqrt(2) - sqrt(10) ) / 2 is negative, and u = ( -sqrt(2) + sqrt(10) ) / 2 is positive.

u = x^2, so u can only be positive. Thus the only solutions are the solutions to

x^2 = ( -sqrt(2) + sqrt(10) ) / 2. The solutions are

x = sqrt( ( -sqrt(2) + sqrt(10) ) / 2 ) and

x = -sqrt( ( -sqrt(2) + sqrt(10) ) / 2 ).

Approximations are x = .935 and x = -.935. **

......!!!!!!!!...................................

RESPONSE -->

I didn't use the quadratic formula. I know the formula and how to use it. I understand how it can be used to get the correct solutions.

self critique assessment: 2

.................................................

......!!!!!!!!...................................

12:31:16

Add comments on any surprises or insights you experienced as a result of this assignment.

......!!!!!!!!...................................

RESPONSE -->

I learned how the quadratic formula can be used to find the solutions to these problems.

confidence assessment: 3

................................................."

&#

Your work looks very good. Let me know if you have any questions. &#